Antitumor effects of Ir(III)-2H-indazole complexes for triple negative breast cancer - Panchangam, Rajeeva Lochana; Rao, Ramdas Nishanth; Balamurali, Musuvathi Motilal; Hingamire, Tejashri B.; Shanmugam, Dhanasekaran; Manickam, Venkatraman; Chanda, Kaushik (Inorganic Chemistry, 2021)
In this work, we have synthesized a series of novel C,N-cyclometalated 2H-indazole-ruthenium(II) and -iridium(III) complexes with varying substituents (H, CH3, isopropyl, and CF3) in the R4 position of the phenyl ring of the 2H-indazole chelating ligand. All of the complexes were characterized by 1H, 13C, high-resolution mass spectrometry, and elemental analysis. The methyl-substituted 2H-indazole-Ir(III) complex was further characterized by single-crystal X-ray analysis. The cytotoxic activity of new ruthenium(II) and iridium(III) compounds has been evaluated in a panel of triple negative breast cancer (TNBC) cell lines (MDA-MB-231 and MDA-MB-468) and colon cancer cell line HCT-116 to investigate their structure–activity relationships. Most of these new complexes have shown appreciable activity, comparable to or significantly better than that of cisplatin in TNBC cell lines. R4 substitution of the phenyl ring of the 2H-indazole ligand with methyl and isopropyl substituents showed increased potency in ruthenium(II) and iridium(III) complexes compared to that of their parent compounds in all cell lines. These novel transition metal-based complexes exhibited high specificity toward cancer cells by inducing alterations in the metabolism and proliferation of cancer cells. In general, iridium complexes are more active than the corresponding ruthenium complexes. The new Ir(III)-2H-indazole complex with an isopropyl substituent induced mitochondrial damage by generating large amounts of reactive oxygen species (ROS), which triggered mitochondrion-mediated apoptosis in TNBC cell line MDA-MB-468. Moreover, this complex also induced G2/M phase cell cycle arrest and inhibited cellular migration of TNBC cells. Our findings reveal the key roles of the novel C–N-cyclometalated 2H-indazole-Ir(III) complex to specifically induce toxicity in cancer cell lines through contributing effects of ROS-induced mitochondrial disruption along with chromosomal and mitochondrial DNA target inhibition.